Implementation of simple additive weighting in determining employee performance based on android at BSI Bank KCP Perbaungan - Tanjung, Mahardika Abdi Prawira; Syafii, Rahmad (Journal of Intelligent Decision Support System (IDSS), 2024)
This study aims to develop and implement a Decision Support System (DSS) based on the Simple Additive Weighting (SAW) method for employee performance evaluation at BSI Bank KCP Perbaungan. The main problems faced by the bank are subjectivity and inefficiency in performance evaluation using manual methods. With this Android-based DSS, employee performance evaluations can be carried out more objectively and transparently, based on criteria such as productivity, work quality, attendance, and teamwork ability. This study involves data collection through observation and interviews with bank management to determine the weights of the criteria used in performance evaluation. The SAW method is then applied to process employee performance data and generate a final score used to identify the best employees. The results show that the SAW method is effective in improving the accuracy and speed of performance evaluations. The implementation of the Android-based DSS simplifies management in handling employee data and generating real-time performance reports. This study concludes that the use of the SAW method in an Android-based DSS can reduce subjectivity in evaluations and improve decision-making efficiency at BSI Bank KCP Perbaungan.